The Cold War Between Medium and Message - Groys, Boris (Javnost-The Public, 2019)
We are still living in the situation informed by the Cold War in art: The Cold War between good and bad, between dispassionate contemplation of the medium and use of this medium for propagation of messages, contents and affects—the war between medium and message. The question remains to what degree it is possible to purify the medium from any content and any affect. To discuss this, I will to turn to the writings by Wassily Kandinsky. Before I show how Kandinsky influenced the further course of the Socialist Realism, I will remind us on the main tenets of his art theory.